Positive affect and age as predictors of exercise compliance - Danilo Garcia; Trevor Archer (PeerJ, 2014)
Physical exercise is linked to individuals whose affect profiles are invariably positive and it induces anti-apoptotic and anti-excitotoxic effects, buttressing blood–brain barrier intactness in both healthy individuals and those suffering from disorders accompanying overweight and obesity. In this regard, exercise offers a unique non-pharmacologic, non-invasive intervention that incorporates different regimes, whether dynamic or static, endurance, or resistance. In this brief report we present a self-reported study carried out on an adolescent and adult population (N = 280, 144 males and 136 females), which indicated that the propensity and compliance for exercise, measured as the “Archer ratio”, was predicted by a positive affect. This association is discussed from the perspective of health, well-being, affect dimensions, and age.